Importance of mining and agriculture in the Peruvian economy - Ccama U., Faustino (2019)
This paper presents a brief description of the Peruvian macro indicators; besides it describes how the Mining and Agriculture sectors impacts on the Peruvian economy, during the last two decades. In this period the Peruvian economy shows an impressive growth 5.44% in terms of gross domestic product (GDP); this period is also known as the ̈mining boom ̈. The excellent performance of mining and agriculture sectors contributed to this economic performance. However, despite the economic growth and changes during the last two decades, extreme poverty, malnutrition and childhood anemia is still a serious problem. To eliminate the extreme poverty Peru has to grow at least 6% per year in terms of GDP. This study proposes that mining and agriculture must keep growing to contribute to the development of Peru. It recommends that private and public investment must increase, it recognizes the importance of competitiveness. Another conclusion is that there is no real conflict between mining and agriculture for water resources; since it is needed by both sectors. This study reviews the economic literature and uses secondary information produced.